2020
DOI: 10.15407/mfint.42.03.0363
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Technological Features of Laser Welding of Titanium-Aluminium Structures on the Microstructure Formation of Welded Joints

Abstract: *-в алюмінієвому стопі від лінії стоплення, **-в титановому стопі від лінії стоплення, ***-фазові виділення по границям.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…They are widely used in medicine (Izonin, Tkachenko, Gregus, Duriagina, & Shakhovska, 2022;Kim, K.-B., Kim, J.-H., Kim, W.-C., Kim, H.-Y., & Kim, J.-H., 2013;Murr et al, 2012;SLM Solutions, 2023), aircraft and rocket engineering (NASA, 2017;Soller et al, 2016), for the manufacture and repair of gas turbine industry parts (Zielinski, 2021), etc. (Shelyagin et al, 2005;Haskin, Bernatskyi, Siora, & Nikulin, 2011;Shelyagin et al, 2021;Fatoba & Jen, 2023;Schlett, 2023).…”
Section: What Is Additive Manufacturing?mentioning
confidence: 99%
“…They are widely used in medicine (Izonin, Tkachenko, Gregus, Duriagina, & Shakhovska, 2022;Kim, K.-B., Kim, J.-H., Kim, W.-C., Kim, H.-Y., & Kim, J.-H., 2013;Murr et al, 2012;SLM Solutions, 2023), aircraft and rocket engineering (NASA, 2017;Soller et al, 2016), for the manufacture and repair of gas turbine industry parts (Zielinski, 2021), etc. (Shelyagin et al, 2005;Haskin, Bernatskyi, Siora, & Nikulin, 2011;Shelyagin et al, 2021;Fatoba & Jen, 2023;Schlett, 2023).…”
Section: What Is Additive Manufacturing?mentioning
confidence: 99%
“…However, Eq. ( 10) is a function of the parameter p, and, taking into account (2), it depends only on the change in the actual position of the spindle (Cpos). Thus, the proposed model of the movement of the transverse axis provides tracking of the actual position of the spindle, regardless of actual speed of its rotation.…”
Section: Mathematical Model Of Motion With Smooth Acceleration In The...mentioning
confidence: 99%
“…These are various parts of transmissions, worm and lead screws, parts of detachable connections and others. The production of such parts is carried out using CNC machining [1][2][3]. High demands are placed on the accuracy of threaded surfaces, which significantly affects both the functional characteristics of products and their reliability and durability, for example [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, laser surface alloying consists in saturating the material with alloying elements by the diffusion of a pre-applied layer under the influence of a laser beam (10 5 -10 6 W/cm 2 ) [6]. It is shown that the laser surface alloying technology contributes to an increase in the wear resistance of iron-carbon alloys by 1.5-3.0 times [7]. Laser surface cladding consists in applying a layer of another material (10 4 -10 6 W/cm 2 ) to the surface, melting the base of the processed material [8].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%